Electrophysiological indices of graded attentional and decision-making processes - Gould, I; Ian Gould (2011)
In everyday life we regularly update our expectations about the locations at which sensory events may occur, and about the motor responses that are appropriate in a given situation. The experiments in this thesis investigated the neural correlates of perceptual processes and motor preparation during human decision making, and the regions that causally contribute to decision making in the human brain. In Chapter 3, I used electroencephalography (EEG) to investigate whether alpha-band (~8-14 Hz) oscillations provide a graded index of participants’ preparatory attentional states. Time-frequency analysis revealed that manipulating spatial certainty regarding the location of an upcoming visual target led to parametric changes in the lateralization of preparatory occipito-parietal alpha oscillations, and to parametric modulation of parieto-central beta-band (~15-25 Hz) power typically associated with response preparation. In Chapter 4, I used EEG to investigate whether evolution of lateralization of sensorimotor alpha- and beta-band activity reflected participants’ evolving expectations about an upcoming motor response. Lateralization of activity in both frequency bands varied parametrically with the available evidence, suggesting such lateralized activity correlates with participants’ internal decision variables. Further analysis identified unique contributions to lateralized and non-lateralized oscillatory activity due to the prior evidence, evidence update, and surprise related to the observed information at each stage of the task. In Chapter 5, I extended the paradigm developed in Chapter 4 for use with online repetitive transcranial magnetic stimulation (TMS) and concurrent EEG recording. Delivery of TMS during decision making allowed investigation of the causal role played by a left hemisphere medial intraparietal region that is the putative human homologue of the macaque medial intraparietal cortex (MIP). MIP stimulation disrupted decision-making behaviour by biasing participants’ decisions against contralateral-to-stimulation (i.e., right-handed) responses. Comparison of the magnitude of TMS-induced changes in behaviour and beta-band activity demonstrated that the intraparietal cortex plays a causal role both in decision making and in the appearance of beta-band activity over the motor cortex. In Chapter 6, the broader consequences of the experimental work presented in this thesis are discussed, in addition to promising directions for future research.